Awareness and approaches of medical doctors and veterinarians on One Health concept. (20th October 2021) - Ozguler, Z; Aslan, D
Abstract: Background: One Health examines health relationships between humans, animals, and ecosystems, but there is a lack of implementation of the concept in health sciences. Medical doctors and veterinarians have crucial roles in improving both the concept and its practices. Therefore, we aimed to understand their awareness, approaches, and recommendations for improvement. Methods: For this descriptive study, data were collected in two subsections. Quantitative data were collected through a form sent via email to members of Ankara Chamber of Medicine and Ankara Chamber of Veterinarians between 24 February and 24 April 2020. The quantitative data on both chambers' board of directors' opinions were obtained through semi-structured interviews on 13 and 22 June 2020. Results: A total of 295 people (74 medical doctors, 221 veterinarians) completed the questionnaire. Most of the doctors (63.5%) and few of the veterinarians (6.3%) had not heard of the concept (p < 0.001). Majority of the veterinarians (7.3%) and a few of the doctors (35.1%) applied the concept (p < 0.001); however, they expressed its usefulness for the health promotion and prevention steps. Although they generally thought that various disciplines and sectors were related to the concept, they had not cooperated with them. Majority of the doctors (95.9%) and veterinarians (71.5%) did not receive any training on One Health (p < 0.001). We also inquired about doctors' and veterinarians' views and suggestions for implementing One Health on components such as scientific research, surveillance, clinical practice, education, health policies, and roles of both medical associations. Proposed views were promising to create collaborative work to advocate One Health approach. Conclusions: We communicated recommendations to integrate the concept into curriculums, create joint training, research, and prioritize cooperation. We planned a panel meeting to discuss the realization of further steps to improve awareness and practice. Key messages: There is a demand by medical doctors and veterinarians for implementing the One Health approach to health-related education and training, surveillance systems, and policies. Medical doctors and veterinarians need collaborative One Health platforms, including other professionals, for information sharing, joint research, prevention, and health promotion practices.